MECHANICAL ANALYSIS OF HIGH-SPEED RAILWAY SLAB BALLASTLESS TRACK UNDER WORKING CONDITION - HE Wei; LI GuiFeng (Jixie qiangdu)
In order to study the mechanical properties of the ballastless track structure under the load of the train, this paper simplified the ballastless track structure to an infinite double-layer elastic beam. The double-layer elastic beam model and its theoretical expression formula was established using the elastic foundation beam concept. When the train was at a certain position on the rail, the differential balance equation between the rail and the concrete slab was established under the action of the vehicle load. Combined with the generalized “initial parameter method” and its boundary conditions, the analytical solution of the double-layer beam displacement and stress were obtained under the vehicle load. Through calculation examples, the displacement and stress of the rail and concrete slab were analyzed, and the analytical results were compared with the results of ANSYS, which proved the reliability of the analytical solution. Therefore, simplifying the slab ballastless track into infinite double-layer elastic beam is closer to the actual working conditions. The results can provide a reliable basis for the theoretical study of the ballastless track of high-speed railways and design reference for related projects.